Evaluasi Implementasi Program Kelas Ibu Hamil (KIH) - Sudarmi, Sudarmi (Jurnal Kesehatan, 2021)
Pregnant Women Class (KIH) is meant to learn together about health for pregnant women, in the form of face-to-face in groups that aim to improve their knowledge and skills. To see it’s the effectiveness of implementation as an effort to develop KIH, it is necessary to evaluate the implementation of KIH. Type of research Evaluation with an evaluation model used to find CIPP which aims to find the Context, Inputs, Processes, and Products of KIH. The technique of collecting data was using study documentation, in-depth interview, observation, and active participation, using a research protocol. Data analysis by data validity and classifying data according to focus and research questions, combining data in the form of matrices or tables and triangulation strategies to describe the results of the analysis and research findings. The results of the evaluation, objectives, process, and implementation of the KIH as a whole have been carried out, but not all activities are by the implementation guidelines that have been set. The focus of activities is not appropriate and requires improvement by evaluation standards, namely the formulation of objectives, setting targets, infrastructure, and the KIH implementation team of facilitators. Recommendations for the implementing team should come from Interprofessional Collaboration (IPC), in the process of implementing the KIH it is expected and suitable with the Standard Operating Procedure (SOP), the need to develop KIH model that is needed for high-risk pregnant women.